Impact of Point-of-Care Testing on the Management of Sexually Transmitted Infections in South Africa: Evidence from the HVTN702 Human Immunodeficiency Virus Vaccine Trial. (17th October 2022) - Asare, Kwabena; Andine, Tsion; Naicker, Nivashnee; Dorward, Jienchi; Singh, Nishanta; Spooner, Elizabeth; Andriesen, Jessica; Osman, Farzana; Ngcapu, Sinaye; Vandormael, Alain; Mindel, Adrian; Abdool Karim, Salim S; et al.
Abstract: Background: Alternative approaches to syndromic management are needed to reduce rates of sexually transmitted infections (STIs) in resource-limited settings. We investigated the impact of point-of-care (POC) versus central laboratory–based testing on STI treatment initiation and STI adverse event (STI-AE) reporting. Methods: We used Kaplan-Meier and Cox regression models to compare times to treatment initiation and STI-AE reporting among HVTN702 trial participants in South Africa. Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) were diagnosed POC at eThekwini clinic and in a central laboratory at Verulam/Isipingo clinics. All clinics used POC assays for Trichomonas vaginalis (TV) testing. Results: Among 959 women (median age, 23 [interquartile range, 21–26] years), median days (95% confidence interval [95%CI]) to NG/CT treatment initiation and NG/CT-AE reporting were 0.20 (.16–.25) and 0.24 (.19–.27) at eThekwini versus 14.22 (14.12–15.09) and 15.12 (13.22–21.24) at Verulam/Isipingo (all P < .001). Median days (95%CI) to TV treatment initiation and TV-AE reporting were 0.17 (.12–.27) and 0.25 (.20–.99) at eThekwini versus 0.18 (.15–.2) and 0.24 (.15–.99) at Verulam/Isipingo (all P > .05). Cox regression analysis revealed that NG/CT treatment initiation (adjusted hazard ratio [aHR], 39.62 [95%CI, 15.13–103.74]) and NG/CT-AE reporting (aHR, 3.38 [95%CI, 2.23–5.13]) occurred faster at eThekwini versus Verulam/Isipingo, while times to TV treatment initiation (aHR, 0.93 [95%CI, .59–1.48]) and TV-AE reporting (aHR, 1.38 [95%CI, .86–2.21]) were similar. Conclusions: POC testing led to prompt STI management with potential therapeutic and prevention benefits, highlighting its utility as a diagnostic tool in resource-limited settings. Abstract : We compared the impact of point-of-care versus centralized laboratory-based testing on managing sexually transmitted infections among HVTN702 vaccine trial participants in South Africa. Point-of-care testing led to faster STI diagnosis, treatment initiation, and reporting of adverse events that were STIs.